The Influence of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on Millenial Generation’s Entrepreneurial Interest - Ani Muttaqiyathun; Yogi Saputra (Prosiding University Research Colloquium, 2022)
The millennial generation, also known as generation Y, is a demographic group after generation X. Many researchers are still debating the exact year of their birth, but most estimate that this generation was born between 1980 and 2000. This generation is now an adult, and has even colored the world. especially in the business sector. Experts believe they have great potential to turn the wheels of the world economy in the near future. This generation has the most control over technology and has the most potential to take the momentum of change in the post-covid-19 era. It was this generation's high interest in pursuing the business world that prompted this research. So this study aims to analyze the role of intellectual intelligence, emotional intelligence and spiritual intelligence on the interest in entrepreneurship for the millennial generation. The object of research is focused on students in the city of Yogyakarta who are still actively studying. The sample is determined at least 15% of the population. Data was collected by means of a questionnaire via googleform. Data analysis used multiple linear regression. The results of the analysis of this study indicate that intellectual intelligence, emotional intelligence and spiritual intelligence have a positive and significant effect either partially or simultaneously on the millennial generation's entrepreneurial interest.